PENGEMBANGAN SUMBER DAYA MANUSIA MELALUI PEMBENTUKAN ORGANISASI DAN PELATIHAN PUBLIC SPEAKING BAGI REMAJA DESA TAMANSARI SETU - Lestary, Maeyke; Novita, Dila; Basri, Hasan (LPPM Universitas Islam 45 Bekasi, 2022)
Human resources who have value and creativity that can easily adapt to technological advances. To produce good human resources, of course, the government does various ways, one of which is to require 12-year schools for the community with the aim of producing human resources that have quality and quantity that are able to compete. With the COVID-19 pandemic, people are forced to do all activities at home, including teenagers. Even though at this age, teenagers need direct interaction with the community so that they can shape the character of the teenager. The formation of adolescent character can be formed through various activities, one of which is by participating in organizational activities. In organizational activities, of course there are conditions where each member is required to be able to speak in public or public speaking. The method used in this research is in the form of counseling and training on public speaking and the formation of youth organizations. The result of this research is that there is a change and increase in knowledge and addition of youth in the organization, and tend to have the courage to convey ideas in public and the formation of an organization for youth.